Comparing Receipt of Social Assistance in Urban and Rural China and the Role of Ethnicity - Björn Anders Gustafsson; Ding Sai (Institute of Labor Economics (IZA), 2021)
Dibao receipt in rural and in urban areas of China is contrasted using household data from seven province-level units. The probability of Dibao-receipt is positively related to how many persons in the household who are older, adults who do not work, and if the household head is not healthy. Means testing of household income is more stringent in urban areas while low household wealth is more important for Dibao-receipt in rural areas. In rural China, membership of the Communist Party of China (CPC) increases the probability of Dibao receipt. A larger proportion ethnic minority households than majority households receive Dibao.
Keywords: I38; J15; P36; 330; China; Dibao; social assistance; income; ethnic minorities